13th FINA World championship finals: stroke kinematics and race times according to performance, gender and event - Jesus, S.; Costa, M. J.; Marinho, D. A.; Garrido, N. D.; Silva, A. J.; Barbosa, T. M. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of this work was to compare the stroke kinematics and race times of the freestyle final races at the 13th FINA World Championships between: (i) the three medalists versus the last three finalists; (ii) males versus female swimmers; (iii) all events in each gender. Data was collected from the championships official web site. There were no significant differences in the stroke kinematics neither in the race times between medalists and non-medalists. There were significant effects in the stroke kinematics and race times according to race event. There were significant effects in the stroke kinematics and race times according to swimmers gender. It seems there are different tactics and biomechanical strategies according to gender and swimming event.